DIMENSI KARAKTER NABI IBRAHIM DALAM AL-QURAN DAN PENDEKATAN TEORI PENDIDIKAN KARAKTER THOMAS LICKONA - Otong Surasman (LP2M Universitas PTIQ Jakarta, 2023)
This research explains the character of the Prophet Ibrahim (AS) in the holy book Al-Quran, as a comparison material for a character theory presented by Thomas Lickona, according to which he can improve human life with ten characters. According to the author, of course it is not enough to just have ten characters, but must refer to the character of the Prophet Ibrahim (AS), where the author found that there are at least 36 characters of the Prophet Ibrahim (AS) in the holy book Al-Quran. Verse after verse provides confirmation of the character of the Prophet Ibrahim (AS), which characters are very important to understand at this time, especially in repairing the wheel of life which is experiencing damage to national morality, which covers the entire world. This research uses a qualitative approach by conducting an in-depth study of the text of the holy book Al-Quran as its main source, which is closely related to the character of the Prophet Ibrahim as. Apart from the holy book Al-Quran as the main reference, we also use tafsir literature to make it easier to understand the character of the Prophet Ibrahim as contained in the holy book Al-Quran. The aim of this research is to obtain actual and factual information regarding the study of the implementation of Thomas Lickona's understanding of the character model of Prophet Ibrahim (AS), then use it as a reference as the main principle in living life, so as to create a life full of love, security, peace and prosperity.